Oxford Guides to Chaucer - Cooper, Helen (Oxford University Press, 2023)
A new edition of Helen Cooper's comprehensive single-volume guide to the The Canterbury Tales, bringing together a wide range of material and providing an accessible commentary on all aspects of the work.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books